Mejoramiento de la inyección de agua de baja salinidad mediante nanopartículas aplicado al recobro mejorado de petróleo (2019)
The injection of water to oil fields is a technique that allows to increase the energy of this, favoring the efficiency of oil recovery. Although, water injection is one of the most used techniques, recently the use of low salinity water has had great scientific attention. However, the mechanisms by which this method works are still not completely clear. On the other hand, the use of nanotechnology in improved oil recovery processes has gained popularity due to the performance it has had in increasing oil production. In this paper, we intend to understand the mechanism of interaction in the crude / brine of low salinity / rock interfaces and in turn, improve the injection of low salinity water with nanoparticles that positively impact the interfacial properties. To achieve what was described, in a first stage of the work the surface-active components were extracted: asphaltenes, resins and naphthenic acids for the preparation of model solutions and evaluation of their effect on the interfacial film. Interfacial tension measurements were made model solution-water and contact angle of cores of varied mineralogical composition to estimate changes in interfacial tension and wettability. These measurements were also performed for dispersions of alumina nanoparticles (nanofluid) in low salinity water. When using the designed nanofluid, a change in the water-oil interfacial tension and contact angle was observed, in addition to a significant increase in oil recovery of 25 and 44% for systems in the absence and presence of nanoparticles, respectively.